Design, Fabrication, Installation, and Population of a Novel Fiberglass Reinforced Plastic Coral Nursery Structure Off the South Shore of O’ahu, Hawaii - Konh, Bardia; Parry, Matthew (Frontiers in Marine Science, 2019)
Coral reefs support a biologically rich ecosystem and are economically invaluable. Unfortunately, due to several reasons including, but not limited to, human activities, global warming effects, and both biotic and abiotic stressors, coral reefs are gradually disappearing from Hawaii’s shorelines. This study introduces novel coral husbandry techniques to help restore injured coral reef habitats. The techniques presented in this work are focused on saving whole coral colonies detached from their bases (via wave action or other physical disturbances) instead of fragmenting existing colonies. Design, fabrication, assembly and installation details of an in-water Fiberglass Reinforced Plastic (FRP) coral nursery structure are discussed in this work. Material selection and novel design of the coral nursery were specifically adapted to physical ocean conditions of the south shore of O’ahu, Hawaii. Factors such as safety, practicality, cost-efficiency, transportation, installation, and attachment of coral colonies for systematic restoration efforts, while maintaining minimal environmental impact, were considered to design and build the coral nursery. Structural fatigue was investigated via finite element methods considering underwater loading and boundary conditions. Fiberglass Reinforced Plastic (FRP) was chosen for the material by a trade-off comparison method. This structure was built, assembled and deployed in south shore O’ahu, Hawaii in April 2018. This study demonstrated the design, engineering and build of a durable coral nursery structure.